Technical and technological support for the involvement of fallow lands in agriculture - S. G. Mitin; G. V. Sysoev; I. A. Starostin; A. V. Eshchin (Бюллетень Почвенного института им. В.В. Докучаева)
Sustainable development of agricultural production is a key factor in ensuring food security and growth of the country's export potential. One of the main reserves for the development of the agro-industrial complex is the involvement of fallow lands in agricultural industry, which is associated with the problem of technical and technological support for these works. The purpose of the work is to intensify the process of involving fallow lands in agriculture by developing a program of technical and technological support for this type of works, aimed at creating and accelerated implementation of a system of specialized machines. The authors systematized technologies and complexes of technical means, used in the involvement of fallow lands in crop production, depending on the stages of wild species overgrowth. For active involvement of fallow lands in agriculture, it is proposed to create a network of regional machine-technological stations equipped with modern domestic specialized equipment, providing services in removal of woody and shrubby vegetation and in initial tillage to agricultural producers in regions. The program assumes the development and organization of mass production of modern equipment for the involvement of fallow lands in agriculture, as well as implementation of a set of support measures aimed at accelerated technical equipment of machine-technological stations. Such an approach should make it possible for small and medium-sized agricultural producers to use financially affordable machinery services to involve fallow lands in agriculture, eliminating the need for its acquisition and maintenance, hiring and training of additional stuff. The implementation of the proposed program should allow agricultural producers to involve fallow lands in agricultural production with minimal costs, at the same time ensuring high growth rates of acreage and agricultural production volumes.